2016
DOI: 10.1111/jicd.12247
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic‐prescribing patterns of South African dental practitioners following tooth extractions

Abstract: The antibiotic prescription patterns of dental practitioners reported in the present study do not appear to follow a coherent set of guidelines or meaningful indications for antibiotic use. The study highlights the need for explicit and more prudent guidelines for the use of antibiotics following tooth extractions, to reduce the risk of antibiotic resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
19
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 21 publications
3
19
2
Order By: Relevance
“…Although, these results differ from those of Lalloo and colleagues (2016), they are consistent with those of Akinbami and Osagbemiro (2015) who found that 55% of healthy patients who underwent routine extractions were prescribed antibiotics. 12,15 The present finding seems to be consistent with other research which found that dentists were more likely to prescribe antibiotics for individuals undergoing extraction of impacted teeth. 12…”
supporting
confidence: 92%
See 4 more Smart Citations
“…Although, these results differ from those of Lalloo and colleagues (2016), they are consistent with those of Akinbami and Osagbemiro (2015) who found that 55% of healthy patients who underwent routine extractions were prescribed antibiotics. 12,15 The present finding seems to be consistent with other research which found that dentists were more likely to prescribe antibiotics for individuals undergoing extraction of impacted teeth. 12…”
supporting
confidence: 92%
“…12,15 The present finding seems to be consistent with other research which found that dentists were more likely to prescribe antibiotics for individuals undergoing extraction of impacted teeth. 12…”
supporting
confidence: 92%
See 3 more Smart Citations